Participative education with nurses: potentialities and vulnerabilities in the breast and cervical cancer tracking - Lidia Santos Soares; Maria da Anunciação Silva; Hayda Josiane Alves; Ana Beatriz Azevedo Queiroz; Irma da Silva Brito
ABSTRACT Objectives: to systematize permanent participatory education experience with Primary Care nurses on breast and cervical cancer screening, identifying potentialities and vulnerabilities. Methods: systematic account according to Holliday, in five stages: starting point, initial questions, recovery of the lived process, background reflection and arrival points. It was the product of two workshops with 96 nurses and analyzed in the light of the ministerial guidelines and Ayres' concept of vulnerability. Results: the potentialities are related to the nurse's work implementing the principles of the Unified Health System. The difficulties are complex and expose individual, contextual and programmatic vulnerabilities in the practice of screening. Final Considerations: permanent education and participatory pedagogical strategies allowed a wide and playful exchange of learning and the participation of a significant number of professionals. There is a need for studies on the institutionality of programmatic guidelines and nurses' space to be the initiator of new practices within the scope of Primary Care.